Pengembangan Sistem Informasi Manajemen Persuratan di Badan Informasi Geospasial - Marliyani, Annisa; Hermawan, Erwin (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2021)
Interpolation is a method to predict new data from existing data. The interpolation method can be used in estimating rainfall because each interpolated point is influenced by the value of the surrounding points. Isohyets are imaginary lines that describe the same amount of rainfall in an area. This map is the result of spatial interpolation of rainfall data. In addition to calculating regional rainfall, an isohyet map can also be used to see the pattern of annual rainfall that occurs. The purpose of this study is to make a map of rainfall in West Java Province so that it can analyze its distribution. The research method used is Waterfall. research conducted at the Meteorology, Climatology and Geophysics Agency regarding the making of rainfall maps in the West Java region on average tenths of a day or based on a map layout using the IDW method that the resulting rainfall pattern is different every tenth of a day. For the level of rainfall (mm) an average of tenths of a day, it can be concluded that in October – March is the rainy season with high rainfall (mm). Meanwhile, April-May is the transition season, namely the escape between the rainy season and the dry season which is in the medium level of rainfall (mm). June – September is the dry season because the level of rainfall (mm) is at a low level